2018
DOI: 10.3892/etm.2018.5979
|View full text |Cite
|
Sign up to set email alerts
|

Soleus muscle H-reflex monitoring in endoscopic surgery under general anesthesia percutaneous interlaminar approach

Abstract: The clinical value of soleus muscle H-reflex monitoring in general anesthesia percutaneous interlaminar approach was investigated. A total of 80 cases with unilateral L5-S1 disc herniation between January 2015 and October 2016 were randomly divided into control group (without soleus muscle H-reflex monitoring, n=40) and observation group (with soleus muscle H-reflex monitoring, n=40). Results showed that the operation time of the observation group was shorter than that of the control group (P<0.05), and the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When conservative treatment fails and disease progression, surgical [18] may be required. Percutaneous transforaminal endoscopic discectomy is a minimally invasive technique for lumbar disc herniation, comparable to open surgery and microendoscopic lumbar discectomy for [18,19] in terms of e cacy.At the same time, it has the advantages of small incision, less bleeding, fast postoperative recovery, and early wake up [11,20,21] . Clinically, epidural and general anesthesia are commonly used for percutaneous transforaminal endoscopic discectomy, but the feasibility, safety and effectiveness of epidural and general anesthesia in patients undergoing percutaneous endoscopic lumbar discectomy are still Therefore, we performed a retrospective cohort study evaluating which type of anesthesia had a better clinical outcome.…”
Section: Test Ow Chartmentioning
confidence: 99%
See 1 more Smart Citation
“…When conservative treatment fails and disease progression, surgical [18] may be required. Percutaneous transforaminal endoscopic discectomy is a minimally invasive technique for lumbar disc herniation, comparable to open surgery and microendoscopic lumbar discectomy for [18,19] in terms of e cacy.At the same time, it has the advantages of small incision, less bleeding, fast postoperative recovery, and early wake up [11,20,21] . Clinically, epidural and general anesthesia are commonly used for percutaneous transforaminal endoscopic discectomy, but the feasibility, safety and effectiveness of epidural and general anesthesia in patients undergoing percutaneous endoscopic lumbar discectomy are still Therefore, we performed a retrospective cohort study evaluating which type of anesthesia had a better clinical outcome.…”
Section: Test Ow Chartmentioning
confidence: 99%
“…General anesthesia General anesthesia GA) and epidural anesthesia (EA) are commonly used in various endoscopic surgeries for [5,6] , and previous studies reported that most clinicians use general anesthesia in order to achieve comfortable and good anesthesia effect.Although patients treated with general anesthesia do not experience pain, they are unconscious and unable to sense neurological damage [7] .Some patients receiving treated epidural anesthesia can not tolerate the pain during surgery [8] .Monitoring of spinal nerve function may provide protective anesthesia against general nerve injury [9][10][11] .However, additional equipment, personnel, and medical costs limit the adoption of the technology to [12] .In recent years, epidural anesthesia has been recommended in percutaneous endoscopic lumbar discectomy to avoid nerve damage because it allows the surgeon to determine whether the nerve root is injured [9,13] based on timely feedback from the patient.How to better manage pain during percutaneous transforaminal endoscopic discectomy has become a major clinical problem facing spine surgeons.…”
Section: Introductionmentioning
confidence: 99%